Udaipur Mineral Basin: A Museum of Minerals and their Environment: Exploring the economic and environmental significance of Udaipur's mineral reserves (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Economy of Udaipur is recognized as a developing economy. Infrastructure development isessential to overall Development of economy of the state. At present minerals is most importantcomponent of infrastructure.A mineral is a naturally occurring, inorganic substance with a definite chemical composition and acrystalline structure. The state is proud to possess huge reserves of Lignite, Crude Oil and High QualityGas. It is also renowned for its deposits of Marble. Mining is not only a major source of employment inthe rural and tribal area of the city.